Modeling the association between psychological capital and nurses’ job performance: The moderating role of intolerance of uncertainty - Seyedeh Melika Kharghani Moghadam; Ehsan Taheri; Ezzat Jafarjalal; Hossein Ebrahimi (PLoS ONE, 2026)
This cross-sectional analytical study aimed to examine the relationship between psychological capital (PsyCap) and nurses’ job performance, as well as the moderating role of intolerance of uncertainty (IU). A total of 212 nurses working in hospitals affiliated with Iran University of Medical Sciences participated. Verbal informed consent was obtained from all participants, as approved by the Ethics Committee of Iran University of Medical Sciences (IR.IUMS.REC.1401.561). Data collection tools included standardized questionnaires on PsyCap, IU, and job performance. Data were analyzed using structural equation modeling (SEM) with SmartPLS software. The measurement model was assessed for reliability and validity, and the structural model was tested for the study hypotheses. The findings indicated that PsyCap was positively and significantly associated with nurses’ job performance (β = 0.38, p < 0.001). IU was not significantly associated with job performance. However, IU negatively moderated the PsyCap–performance relationship (β = −0.16, p = 0.005). These findings suggest that PsyCap may be positively related to nurses’ job performance, although its positive effects may be attenuated under high IU. Interventions aimed at strengthening PsyCap alongside uncertainty-management strategies may help optimize performance in clinical settings.